Improving the Efficiency of Macroeconomic Systems by Spurring up - Irina P. BOGOMOLOVA; Elena I. KRIVENKO; Maria B. CHIRKOVA; Julia N. VORONTSOVA; Elena S. STRYAPCHIKH (Communications of International Proceedings, 2020)
As the national economy transits to a resource saving model the need for tailoring managerial methods, principles and approaches for the strategic goal becomes urgent. With that in mind, this research analyses resource saving efficiency of producing systems at the macroeconomic level, including analysis of changes in energy intensity of the economy; we cite depreciation indicators of fixed assets of high, medium and low degree of technology; we have calculated the coefficient of fixed assets upgrade in the Russian Federation; we outline the dynamics of creation, utilization, neutralization and disposal of production and consumption wastes in Russia; changes in the environmental operating costs in the Russian Federation; we  have calculated the share of R&D costs on the priority directions of science, technology and engineering in the total spending on R&D for the country in general; we have defined innovation activity of the Russian companies; the share of companies with technological innovations; the number of created advanced, new and fundamentally new production technologies in Russia; the share of energy resources produced with the use of renewable energy sources in the total volume of the Russian Federation’s  energy resources. We have formulated a conceptual goal of spurring up Russia’s resource saving activities by way of conclusion.
Keywords: Economy; Management; Resource Saving; Mechanism; Effectiveness; Intensification; Research